Physicians and pharmacists' clinical knowledge of statin therapy and monitoring parameters, and the barriers to guideline implementation in clinical practice - Al-Ashwal, Fahmi Y.; Syed Sulaiman, Syed Azhar; Sheikh Ghadzi, Siti Maisharah; Kubas, Mohammed Abdullah; Halboup, Abdulsalam (Public Library of Science (PLOS), 2023)
Background Millions of individuals worldwide use statins, and their significant impact on cardiovascular disease (CVD) has been well-established. However, a lack of knowledge about the up-to-date guideline recommendations regarding statin therapy is a common barrier to implementation in clinical practice. Therefore, the present study aimed to assess the current clinical knowledge about statin therapy and its monitoring parameters. Also, we evaluated the barriers to cholesterol management guideline implementation in Yemen. Methods This observational cross-sectional study was conducted over four months, from June/2021 to September/2021, in Sanaa, Yemen. A validated questionnaire was distributed face-to-face to 650 participants (350 physicians and 300 pharmacists). Physicians and pharmacists from governmental and private hospitals and those working in private clinics or community pharmacies were included in the study. Results A total of 496 participants filled out the survey, with 22 being excluded due to incomplete data. So, the study has an overall response rate of 72.9% (474). The majority of pharmacists (81.8%) and physicians (78.7%) could not identify the patient group that needed ASCVD risk assessment before statin therapy initiation. Although a significant proportion of respondents knew of the fact that high-intensity statins are recommended for patients with ASCVD (65.4%) and primary hypercholesterolemia (58.4%), the majority of physicians and pharmacists could not identify the high (61.6% and 66.7.3%, respectively) and moderate statin-intensity doses (72.2% and 68.6%, respectively). Only 21.9% of all respondents knew that atorvastatin and rosuvastatin can be administered at any time of the day. Similarly, a low overall rate of respondents (19.6%) knew that atorvastatin does not need dose adjustment in chronic kidney diseases, with a statistically significant difference in knowledge between physicians and pharmacists (12.5% vs. 25.6%, p <0.001, respectively). Notably, only 39.2% of participants were aware that statins are not safe to use during breastfeeding. Around half of respondents (52.3%) correctly identify the duration (4 to 12 weeks) at which LD-C measuring is recommended after therapy initiation or dose change. The lowest knowledge scores for respondents were related to statin-drug interactions. Age, experience, degree, and previous guideline exposure were all significantly associated with the knowledge scores (p <0.05). The four most perceived barriers to implementing cholesterol management guidelines were no audit on adherence to the guidelines in the workplace (73.4%), insufficient resources to adequately implement and follow up on the guidelines recommendations (73.6%), patients financial status (75.7%), and lack of familiarity about the guidelines latest recommendations (63.3%). Conclusion Physicians and pharmacists had suboptimal clinical knowledge regarding statin therapy, dose intensities, drug-drug interaction, contraindications, and monitoring parameters. Therefore, physicians and pharmacists educational interventions regarding the up-to-date recommendation about statins are recommended.